ANALISIS HASIL WAWANCARA MENGENAI STANDAR SARANA DAN PRASARANA UNTUK MENGETAHUI LINGKUNGAN BELAJAR DI SDN PINAYUNGAN IV - Nandia Latifah; Revan Anggara; Rima Mulhimawati; Siti Nabilah; Hinggil Permana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the availability and condition of facilities and infrastructure at SDN Pinayungan IV, Karawang. The research method employed participant observation and interviews with the principal, sixth-grade teachers, and sixth-grade students. The observation results indicate that the school still faces facility limitations, such as an insufficient number of classrooms, limited toilets, and the absence of a prayer room (musholla), library, and science laboratory. Existing facilities such as the teachers’ room, sports field, and reading corner do not yet fully meet national standards. The study concludes that there is a gap between the educational facility standards set in the Regulation of the Minister of National Education (Permendiknas) No. 24 of 2007 and the actual conditions in the field. It is recommended that the school, the Department of Education, and relevant stakeholders increase their attention and efforts to fulfill the necessary facilities and infrastructure to support the quality of learning.